Pengaruh Cita Rasa, Kualitas Pelayanan, Etika Pelayanan Dan Lokasi Usaha Terhadap Kepuasan Pelanggan Pada UMKM Warung Kopi Gelas Batu Kota Pinang - Putri, Noni Adetiansi; Safri, Hayanuddin; Zufri, Zufri (Universitas Labuhanbatu, 2021)
This study was conducted to determine and analyze the influence of taste, service quality, service ethics and business location on customer satisfaction at the UMKM Kopi Kaca Batu Pinang City. The population in this study were all customers of the glass coffee shop in Kota Pinang, with sampling using the slovin formula. Then the data collection technique uses a questionnaire/questionnaire as an instrument or research tool by testing the validity and reliability first. Furthermore, to analyze the data using the classical assumption test in the form of normality test, multicullinearity test and heteroscedasticity test. The results showed that the taste (X1) had a positive and significant effect on customer satisfaction (Y) in the UMKM at the glass coffee shop in Pinang City with a t_count value of 2,338 with a significant level of 0.022 0.05. Quality of service (X2) has a positive and significant effect on customer satisfaction (Y) in the MSME glass coffee shop in Pinang City where the t_count value is 2.557 with a significant level of 0.012 0.05. Service ethics (X3) has a positive and significant influence on customer satisfaction (Y) in the MSME glass coffee shop in Pinang City where the t_count value is 2.063 with a significant level of 0.045 0.05. The location of the business (X4) has a positive and significant influence on customer satisfaction (Y) in the MSME glass coffee shop in Pinang City where the t_count value is 2.059 with a significant level of 0.034 0.05. taste, service quality, service ethics and business location together (simultaneously) affect customer satisfaction (Y) with a value of F_count (11,600) > F_table (2.469) and a significance level of 0.003 0.05 with a confidence level of 72.7 % and an error rate of 27.3%.